Hearing about a story character's negative emotional reaction to having been dishonest causes young children to cheat less. Issue 2 (26th August 2022) - Zhao, Li; Li, Yingying; Sun, Wenjin; Zheng, Yi; Harris, Paul L.
Abstract: There is extensive research on the development of cheating in early childhood but research on how to reduce it is rare. The present preregistered study examined whether telling young children about a story character's emotional reactions towards cheating could significantly reduce their tendency to cheat ( N = 400; 199 boys; Age: 3–6 years). Results showed that telling older kindergarten children about the story character's negative emotional reaction towards rule violation significantly reduced cheating, but telling them about the positive emotional reaction towards rule adherence did not. These results show that children as young as age 5 are able to use information about another child's emotional reaction to guide their own moral behavior. In particular, highlighting another child's negative emotional reaction towards a moral transgression may be an effective way to reduce cheating in early childhood. This finding, along with earlier cheating reduction findings, suggests that although cheating is common in early childhood, simple methods can reduce its occurrence. Abstract : We examined whether telling children between 3 and 6 years of age (total N = 400; 199 boys) about a story character's emotional reactions towards cheating could significantly reduce their tendency to cheat. Results showed that telling 5‐ to 6‐year‐old children about the story character's negative emotional reaction towards rule violation significantly reduced cheating, but telling them about the positive emotional reaction towards rule adherence did not. These results show that children as young as age 5 are able to use information about another child's emotional reaction to guide their own moral behavior, and that highlighting another child's negative emotional reaction towards a moral transgression may be an effective way to reduce cheating in early childhood.